Stable human FIX expression after 0.9G intrauterine gene transfer of self-complementary adeno-associated viral vector 5 and 8 in macaques - Mattar, Citra Nurfarah Zaini; Nathwani, Amit C; Waddington, Simon N; Dighe, Niraja; Kaeppel, Christine; Nowrouzi, Ali; Mcintosh, Jenny; Johana, Nuryanti B; Ogden, Bryan; Fisk, Nicholas M; Davidoff, Andrew M; David, Anna; et al. (Molecular therapy, 2011)
Intrauterine gene transfer (IUGT) offers ontological advantages including immune naiveté mediating tolerance to the vector and transgenic products, and effecting a cure before development of irreversible pathology. Despite proof-of-principle in rodent models, expression efficacy with a therapeutic transgene has yet to be demonstrated in a preclinical nonhuman primate (NHP) model. We aimed to determine the efficacy of human Factor IX (hFIX) expression after adeno-associated-viral (AAV)-mediated IUGT in NHP. We injected 1.0-1.95 × 1013 vector genomes (vg)/kg of self-complementary (sc) AAV5 and 8 with a LP1-driven hFIX transgene intravenously in 0.9G late gestation NHP fetuses, leading to widespread transduction with liver tropism. Liver-specific hFIX expression was stably maintained between 8 and 112% of normal activity in injected offspring followed up for 2-22 months. AAV8 induced higher hFIX expression (P = 0.005) and milder immune response than AAV5. Random hepatocellular integration was found with no hotspots. Transplacental spread led to low-level maternal tissue transduction, without evidence of immunotoxicity or germline transduction in maternal oocytes. A single intravenous injection of scAAV-LP1-hFIXco to NHP fetuses in late-gestation produced sustained clinically-relevant levels of hFIX with liver-specific expression and a non-neutralizing immune response. These data are encouraging for conditions where gene transfer has the potential to avert perinatal death and long-term irreversible sequelae.